Superoxide dismutase ameliorates oxidative stress and regulates liver transcriptomics to provide therapeutic benefits in hepatic inflammation - Chen, Longyan; Liu, Yang; Zhang, Yonggang; Zhang, Yanmin; Wang, Wei; Han, Hongyu; Yang, Chunyu; Dong, Xueqian (PeerJ, 2023)
Background Oxidative stress refers to the imbalance between oxidants and antioxidants in organisms and often induces hepatic inflammation. Supplementing exogenous superoxide dismutase is an effective way to alleviate oxidative stress; however, the effects and mechanisms by which superoxide dismutase alleviates hepatic inflammation remain unclear. Methods This study established a Kunming mouse model to verify and investigate the oxidative stress and hepatic inflammation-alleviating effects of the superoxide dismutase oral supplement that was prepared by our research group in a previous study. Results The superoxide dismutase product significantly restored the body weight and liver alanine transaminase, aspartate aminotransferase, superoxide dismutase, catalase, glutathione, and glutathione peroxidase levels of oxidative stress induced mice. Moreover, exogenous superoxide dismutase significantly inhibited interleukin 1β and interleukin 6 mRNA expression in the livers of mice with hepatic inflammation. Transcriptomic analysis indicated that superoxide dismutase had a significant inhibitory effect on Endog expression, alleviating oxidative stress damage, and mediating liver cell apoptosis by regulating the expression of Rab5if, Hnrnpab, and Ifit1. Conclusion Our research verified the oxidative stress remediation effects of superoxide dismutase and its therapeutic role against hepatic inflammation. This study can lay a foundation for investigating the mechanism by which superoxide dismutase alleviates hepatic disease.
Keywords: Superoxide dismutase; Oxidative stress; Hepatic inflammation; Transcriptomics; Deoxynivalenol